Bioinspired Iron‐Based Catalyst for Atom Transfer Radical Polymerization1. Issue 46 (23rd September 2013) - Simakova, Antonina; Mackenzie, Matthew; Averick, Saadyah E.; Park, Sangwoo; Matyjaszewski, Krzysztof
<x xml:space="preserve">Abstract</x> Naturally occurring hemin, an iron‐containing porphyrin, and its synthetic derivatives were used as atom transfer radical polymerization (ATRP; see picture) catalysts. The effects of the halide salt concentration, attachment of poly(ethylene glycol) moieties, and hydrogenation of the hemin vinyl groups on the catalyst performance were studied.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>